Investigating biodiesel production strategies as a sustainable energy resource for Pakistan. (20th June 2020) - Ali, Shahzad; Fazal, Tahir; Javed, Fahed; Hafeez, Ainy; Akhtar, Mueed; Haider, Bilal; Saif ur Rehman, Muhammad; Zimmerman, William B.; Rehman, Fahad
Abstract: Over reliance on fossil fuels to meet the ever increasing energy demands has adversely affected the economy and environment of Pakistan. The transportation sector is the major consumer of these imported petroleum products. Among these petroleum products, high speed diesel and gasoline are the most consumed. Bio-fuels, produced from indigenous biomass, can surmount the twofold problem of deteriorating environment and sustainable supply of energy resource. As an agricultural country, Pakistan prodigiously produces biomass (e.g. animal dung, molasses and bagasse) which can replace natural gas, gasoline and electricity conventionally produced from fossil fuels. However, an alternative to high speed diesel has not been identified yet. This review paper is focused on developing a strategy for identifying potential biodiesel feed-stocks suitable for Pakistan and their contribution towards "the solution" of sustainable energy and environment. The selection parameters for feedstock, land, irrigation, oil yield, composition and maturation duration are discussed in detail. Based on agro-climatic conditions of the Pakistan, castor and jatropha cultivated on water scarce lands are lucrative feed stocks for bio-diesel. Moreover, by-products of both these feed stocks like seed cake and glycerine are explored for production of gaseous fuel such as bio-gas or hydrogen, electricity generation and animal meal production which can render biodiesel economically viable. An integrated approach for biodiesel production associated with by-products utilization has been proposed. Graphical abstract: Image 10634 Highlights: Latest trends of fossil and renewable energy mix in Pakistan has been discussed. Availability of land in accordance with agro-climatic conditions is evaluated. Crop and oil yields are significantly affected by soil fertility and rain per year. Co-cultivation with castor for short term and jatropha for longer term is suggested. A strategy integrating biodiesel production and by-products utilization is proposed.